Overtreatment of Heparin-Induced Thrombocytopenia in the Surgical ICU*. Issue 1 (January 2017) - Harada, Megan Y.; Hoang, David M.; Zaw, Andrea A.; Murry, Jason S.; Volod, Oksana; Sun, Beatrice J.; Nuño, Miriam; Mason, Russell; Margulies, Daniel R.; Ley, Eric J.
Abstract : Objective: Recent studies reveal a high occurrence of overdiagnosis of heparin-induced thrombocytopenia in surgical patients with critical illness. The optimal criteria for diagnosis of heparin-induced thrombocytopenia remain unclear, contributing to unnecessary treatment. We reviewed patients who were admitted to surgical ICUs and were suspected of heparin-induced thrombocytopenia to identify how often patients were correctly treated. Design: In this clinical prospective study, data were collected including age, sex, antiplatelet factor 4/heparin enzyme-linked immunosorbent assay, serotonin release assay, and Warkentin 4Ts scores. Heparin-induced thrombocytopenia-positive patients were defined as those with both positive antiplatelet factor 4/heparin enzyme-linked immunosorbent assay (optical density, ≥ 0.40) and positive serotonin release assay results. Setting: Urban tertiary medical center. Patients: Patients admitted to the surgical and cardiac ICU who were presumed to have heparin-induced thrombocytopenia and underwent antiplatelet factor 4/heparin enzyme-linked immunosorbent assay and serotonin release assay testing between January 1, 2011, and August 1, 2014. Interventions: None. Measurements and Main Results: A total of 135 patients had 4Ts, antiplatelet factor 4/heparin enzyme-linked immunosorbent assay, and serotonin release assay scores. A total of 11 patients (8.1%) had positive serotonin release assay and 80 patients had positive antiplatelet factor 4/heparin enzyme-linked immunosorbent assay; 10 patients were identified as heparin-induced thrombocytopenia positive. Positive serotonin release assay was noted in nine of 11 patients (81.8%) with antiplatelet factor 4/heparin enzyme-linked immunosorbent assay optical density greater than or equal to 2.0, compared with one of 22 patients (4.5%) with optical density values of 0.85–1.99, and one of 102 patients (1.0%) with optical density values of 0–0.84. Out of 135 patients, 29 patients (21.5%) received treatment with argatroban, lepirudin, or fondaparinux: 10 of 10 heparin-induced thrombocytopenia-positive patients (100%) compared with 19 of 125 heparin-induced thrombocytopenia-negative patients (15%). Conclusions: Overtreatment of heparin-induced thrombocytopenia in the surgical ICU continues even with recent increased caution encouraging a higher antiplatelet factor 4/heparin enzyme-linked immunosorbent assay optical density threshold before initiating treatment. More stringent criteria should be used to determine when to order serologic testing and when the results of such testing should prompt a change in anticoagulant treatment. If antiplatelet factor 4/heparin enzyme-linked immunosorbent assay is used to consider immediate treatment, an optical density greater than or equal to 2.0 may be a more appropriate threshold.